Normative Value of Arch Index in Elderly- A Cross Sectional Study - Pornak, Miss. Vaishali R.; Nikhade, Dr. Nitin S. (International Journal of Innovative Research in Medical Science, 2017)
Background: The Medial longitudinal arch (MLA) is a very important structure of the foot. As age advances it undergoes some anatomical and biomehanical changes. Body mass index may have its effect on the MLA. Till date Normal values of arch Index have not yet been established in elderly Indian population and Body Mass Index (BMI) may influence the Arch Index. Aims and objectives: To find the normative values of Arch Index and to find its correlaion with BMI. Method: A cross sectional study was conducted among the community dwelling elderly of Ahmednagar district. 100 elderly (50 Males & 50 Females) in the age group of 60-85 years were included in the study. The demographic data was collected and measurements of Arch Index were taken to find out normative values. Results: The normative values of Arch Index were 0.352(0.21, 0.44) on right foot and 0.354(0.19, 0.48) on left foot in both the genders. There was no correlation of BMI with Arch Index on both sides. Conclusion: The normative value of arch index in elderly is 0.35 in both males and females and Arch index has no correlation with BMI.